Answer:
2.54 m/s
Step-by-step explanation:
By conservation of energy,
work done by force due to hand = mechanical energy gained by yo-yo
So Fd = mgh + 1/2m(v₂² - v₁²)
where F = force on string = 0.19 N, d = distance moved by hand = 0.12 m, m = mass of yo-yo = 0.058 kg, g = acceleration due to gravity = 9.8 m/s², h = distance moved by yo-yo = 0.30 m, v₁ = initial speed of yo-yo = 3.4 m/s and v₂ = final speed of yo-yo = unknown
So, Fd = mgh + 1/2m(v₂² - v₁²)
Fd/m = gh + 1/2(v₂² - v₁²)
Fd/m - gh = 1/2(v₂² - v₁²)
2(Fd/m - gh) = (v₂² - v₁²)
(v₂² - v₁²) = 2(Fd/m - gh)
v₂² = v₁² + 2(Fd/m - gh)
taking square-root of both sides, we have
v₂ = √[v₁² + 2(Fd/m - gh)]
Substituting the values of the variables into the equation, we have
v₂ = √[(3.4 m/s)² + 2(0.19 N × 0.12 m/0.058 kg - 9.8 m/s² × 0.30 m)]
v₂ = √[(3.4 m/s)² + 2(0.19 N × 0.12 m/0.058 kg - 9.8 m/s² × 0.30 m)]
v₂ = √[(3.4 m/s)² + 2(0.0228 Nm/0.058 kg - 9.8 m/s² × 0.30 m)]
v₂ = √[(3.4 m/s)² + 2(0.393 Nm/kg - 2.94 m²/s²)]
v₂ = √[(3.4 m/s)² + 2(-2.547 m²/s²)]
v₂ = √[11.56 m²/s² - 5.094 m²/s²)]
v₂ = √[6.466 m²/s²]
v₂ = 2.54 m/s